Multi-level characteristics recognition of cancer core therapeutic targets and drug screening for a broader patient population - Su, Yangguang; Wang, Ying; Qu, Zhuo; Liu, Jiaxin; Ren, Xuekun; Zhang, Denan; Chen, Xiujie (Frontiers in Pharmacology, 2023)
Targeted therapy for mutations in cancer cells has highlighted issues such as the scarcity of therapeutic targets, the small number of patients who benefit, and the susceptibility to acquired drug resistance, which have become major challenges in clinical applications. Synthetic lethality (SL)based targeted therapies have shown promise in targeting cancers with specific mutations due to their clear biological mechanisms and high specificity. However, synthetic lethal therapeutic targets for cancer cells that are truly lethal are still rare due to the existence of compensatory mechanisms. To this end, this study exploits the different levels and dimensions of cancer characterization to identify core therapeutic targets (CTTs) with extensive synthetic lethality in cancer and their potential therapeutic drugs based on synthetic lethality mechanisms, considering the regulation of cancerspecific genes at the transcriptional and post-transcriptional levels, by constructing a model incorporating statistics and machine learning. The results of this study are well generalizable and the model identifies potential therapeutic targets by learning the characteristics of known synthetic lethal gene pairs in different dimensions and histological data, combining statistical screening and network analysis to improve the confidence of potential targets. In other cancers, we used the same process to identify corresponding CTTs and potential therapeutic drugs in lung and renal cell carcinoma, which have completely different histogenetic origins and analyzed the therapeutic targets common to all three cancers. Our approach provides new theoretical insights and methodological support for the identification of core therapeutic targets and drugs for targeted therapies in different cancer types.